A novel ultrasonic crushing method for accurate detection of viable spore counts in Paenibacillus polymyxa-based microbial pesticides is superior to the conventional method of Shaker shaking. Issue 3 (4th March 2023) - Guo, Jiacai; Ling, Jie; Zhang, Kaikai; Fan, Fei; Wang, Weiliang; Luo, Yuanchan; Wan, Minxi; Li, Yuanguang
ABSTRACT: The number of viable spores is the most important quality index of Bacillus -based microbial pesticides. This study aimed to establish a novel pre-treatment method of samples for improving the traditional plate counting method thereby detecting the number of viable spores accurately and reproducibly in Paenibacillus polymyxa -based microbial pesticides. Firstly, three pre-treatment methods of Shaker shaking (SSP), ultrasonic oscillation (UOP), and ultrasonic crushing (UCP) were optimised and compared. The results showed that only the UCP-based plate counting method could detect accurately the viable spore counts (5.2 × 10 9 CFU/g) in the 5 × 10 9 CFU/g P. polymyxa original powder, and were repeated well with a coefficient of variation (CV) of 5.0%, compared to SSP (3.46 × 10 9 CFU/g, CV was 23.4%) and UOP (3.5 × 10 9 CFU/g, CV was 26.0%). The optimal conditions of UCP were ultrasonic power of 200 W, ultrasonic/intermittent time of 3 s/3 s, and total time of 3 mins (30 cycles). Furthermore, the scanning electron microscope observed that spores were completely desorbed from the carrier by the UCP method. and the average particle size of the carrier pellet was about 2–5 μm, which is significantly smaller than the average particle size of the carrier pellet without pre-treatment (about 15–20 μm) and by the SSP (about 7–12 μm). The plate counting method based on UCP could desorb all spores from the carrier, and the detection results of viable spore counts in P. polymyxa microbial pesticides were accurate and reproducible.